2012
DOI: 10.5325/transportationj.51.3.0338
|View full text |Cite
|
Sign up to set email alerts
|

Air Traffic Controllers' Situation Awareness and Workload under Dynamic Air Traffic Situations

Abstract: As air-traffic control (ATC) services are provided for the purpose of achieving flight safety and efficient aircraft operations, the role of air-traffic controllers in the aviation system is vital. Since the accident rates caused by human error have been increasing, major aviation institutes worldwide are actively conducting research on the human factors affecting controllers. Among human factors in aviation, situation awareness (SA) and workload have been at the center of many research activities for years. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
7
2
Order By: Relevance
“…Such interferences have been reported in relation with health complaints (Cascino and Mélan, 2019) and stress the interest of considering in future shiftwork studies measures that provide information about participants' fitness outside working hours. Moreover, the reported sleep duration did not change according to traffic load, in contrast to the results reported in other studies (Åkerstedt et al, 2002;Corver et al, 2016;Nealley and Gawron, 2015;Lee et al, 2012).…”
Section: Assessment Of the Results With Regards To The Research Quest...contrasting
confidence: 83%
See 2 more Smart Citations
“…Such interferences have been reported in relation with health complaints (Cascino and Mélan, 2019) and stress the interest of considering in future shiftwork studies measures that provide information about participants' fitness outside working hours. Moreover, the reported sleep duration did not change according to traffic load, in contrast to the results reported in other studies (Åkerstedt et al, 2002;Corver et al, 2016;Nealley and Gawron, 2015;Lee et al, 2012).…”
Section: Assessment Of the Results With Regards To The Research Quest...contrasting
confidence: 83%
“…Hence, the aim of the present study was to investigate the effects of both shift-schedule arrangements and traffic load on ATCOs' sleep, fatigue and alertness. A significant effect of traffic load was expected, with increased sleep length and alertness and reduced fatigue for lower aircraft traffic (Åkerstedt et al, 2002;Corver et al, 2016;Nealley and Gawron, 2015;Lee et al, 2012). We hypothesized that the beneficial effect would be most marked for morning shifts, as reduced traffic may counterbalance the well-known deleterious effects associated with early morning shift beginning (Tucker et al, 1998).…”
Section: Study Aimsmentioning
confidence: 94%
See 1 more Smart Citation
“…Endsley [29] questions the design of the SART questionnaire, which would evaluate cognitive processes close to MW. Another hypothesis supported by some authors [22,30,31] is that a high but reasonable MW would be necessary to achieve a high level of SA. Future research could attempt to test our model using more appropriate measurement methods for assessment in a real surgical context.…”
Section: Situation Awareness Mental Workload and Stressmentioning
confidence: 94%
“…The theoretical link between MW and SA has been discussed for several decades. Endsley [8] posits that SA and MW are two independent concepts, while others [17,23] suggest that the two concepts are interdependent, especially when MW is high. Various researchers have tested the relationships that may exist between these two notions [1,13,18,41], and a meta-analysis [40] concluded that the MW-SA relationship varies depending on the context.…”
Section: Factors Influencing Samentioning
confidence: 99%